Impact of Data Source on Evapotranspiration Calculation: On-Site Vs. METMalaysia Weather Stations - Fazlil Ilahi, Wan Fazilah; Rosdi, Nur Syaffiqa Izleen; Shahemi, Muhammad Hazim (International Journal of Integrated Engineering, 2025)
Crop water requirement is the estimation of water that needs to be replenished due to the crop evapotranspiration (ETc) by the crop. This process is critical for ensuring adequate irrigation and maximizing crop yield. In Malaysia, climate data from Malaysia Meteorological Department (METMalaysia) stations are commonly used for ETc estimation. Although these METMalaysia stations are not located directly within the plantation area, these data are easily accessible and widely utilized for ETc calculation. However, misleading climate data will result in a wrong estimation of evapotranspiration (ET), which may lead to over or under-irrigation, resulting in plant damage thus decreasing the yield. Durian (Durio zibethinus), known as the “king of fruits”, holds significant economic importance in Malaysia due to its high demand in both domestic and export markets across ASEAN countries. Understanding the ET of durian is essential for optimizing irrigation practices and enhancing crop revenue for farmers. The objective of this study is to compare ETc from climate data consisting of daily minimum and maximum temperature, humidity, wind speed, and sun radiation, obtained from on-site weather station and METMalaysia weather station. This study is conducted in a durian plantation at Durian Valley, Kluang, Johor. Data analyses were conducted using a T-test. The result shows a significant difference between calculated ETc using climate data obtained from the on-site weather station compared to data from the METMalaysia weather station which emphasizes the importance of accurate, location-specific climate data for effective irrigation management in durian cultivation.